(untitled) (Pakistan Journal of Engineering, Technology and Science, 2024)
Gesture recognition systems have become increasingly popular in recent years due to their ability to improve the user experience and accessibility in real time. However, accurate and efficient hand gesture recognition remains a challenge, especially in dynamic environments. This study presents real-time hand gestures and poses using computer vision. Fundamentally, the system can identify and categorize a wide range of hand movements through real-time analysis of the node connect points of the user’s fingers. Every successive point is rendered in such a way that associations between several points have been oriented, and differences between each gesture may be classified. Apart from this, the machine learning model is to be trained on such joint points of the user’s fingers using angle approximation in between them and gradient as per pixels per inch according to a hand gesture-capturing adapter like a camera. For this task to be done, we aim to use the Support Vector Machine (SVM) algorithm for recognizing the classifying parameters of live gestures. The study utilizes support vector machines (SVM) to deliberately cluster signals according to their node focuses. To enhance the accuracy and resilience of the whole model, a support vector machine is incorporated into the classifier to maximize the classification function of the courier-based domain.